Calculation of inter-provincial differences in the appropriate proportioning of land transfer income to support rural revitalization - Wang, Yubo; Xue, Yuyu (Frontiers in Environmental Science, 2022)
This research examined the suitability and regional differences of the distribution ratio of land transfer income aimed at supporting rural revitalization via calculating the distribution ratio of 31 provincial-level administrative divisions (abbreviated as 31PLAD), while also providing a reference template for land transfer incomes. Herein, we collated and calculated the fiscal expenditure of five dimensions of each province (city, district) in 2005, 2010, 2015, and 2020, and then predicted the situation of the next period (that is, 2025) using GM (1, 1). Further, we used a time series to calculate the land transfer income of each province in 2025. After combining these two, the possible support of land transfer income in all dimensions of rural revitalization across the 31PLAD in 2025 was calculated. Then, according to the Dagum Gini coefficient method, the regional differences of each dimension across the 31PLAD were observed. The financial expenditure of the 31PLAD across the five dimensions studied revealed that the expenditure of industrial prosperity and its proportion are higher, followed by the dimensions of ecological livability and rural civilization. The expenditure of the other dimensions, except for that of affluence in Regions I and II, is better than that of the same dimension in the region. The overall differences among the 31PLAD represent low industrial prosperity, high affluent life, similar overall differences between rural civilization and effective governance, and relatively large differences in ecological livability. Our findings provide relevant suggestions that would help to effectively support rural revitalization.